Performance Audit of Prevention and Control of Diseases Programme in Mizoram - CAG of India (CAG of India, 2002)
The National AIDS Control Programme came into effect in 1987 with assistance from World Bank. In the first phase, the programme was initially launched for a period of 5 years starting from September 1992 to September 1997. But due to slow utilisation of the fund in the first two years of its implementation, it was extended till March 1999. The Government of India (GOI), in March 1999, launched Phase II of the Programme for a period of another five years upto the end of October 2004; The National Leprosy Control Programme was launched in the country by GOI in 1954-55 and subsequently, it was re-designated as NLEP and came into effect in the year 1983; The NPCB was launched by GOI in the year 1976 and the NTBCP was launched by GOI in 1962. In 1992, this programme was reviewed by a Committee of experts and based on the report of the review committee, a revised strategy for NTBCP was evolved and the GOI decided to extend the programme throughout the country in a phased manner. The performance audit of Prevention and Control of Diseases Programme in Mizoram for the period 1996-97 to 2000-01 highlighted failure of the state government to obtain and utilise the full amount of sanctioned grant of Rs.712.41 lakh from the Government of India during the years 1996-1997 to 2000-2001 under the National AIDS Control Programme, lack of proper monitoring in respect of National Leprosy Eradication Programme (NLEP), National Programme for Control of Blindness and National TB Control Programme for effective implementation of these programmes and shortfall in achievement of targets fixed for different components of these programmes.
For the Period 1996-97 to 2000-01